PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP PENINGKATAN HASIL BELAJAR SISWA DI SMK NEGERI 3 TONDANO - david sangari; Hendrik Sumarauw; Lenie Ratag (GEARBOX: Jurnal Pendidikan Teknik Mesin, 2021)
PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP PENINGKATAN HASIL BELAJAR SISWA DI SMK NEGERI 3 TONDANO Oleh : David G. Sangari 14212081 Dosen Pembimbing : Drs. H. J. R. Sumarauw, M.Pd Dra. Lenie Ratag, M.Pd ABSTRAK David G. Sangari. 2019. The Influence of the Snowball Throwing Learning Model on the Improvement of Student Learning Outcomes at SMK Negeri 3 Tondano. Thesis, PTM S-1 Study Program, Faculty of Engineering. University Manado State. Advisors (1) Drs. H. J. R. Sumarauw, M.Pd, (II) Dra.Lenie Ratag, M, Pd Keywords: Snowball Throwing Model, Competency Learning of Light Vehicle Engineering Skills Based on the observations of researchers in the field, students in the learning process centered only on teachers and students only memorized concepts. The results at this reflection stage would be the basis for making improvements in this study. This study used 2 classes, namely the experimental class and the control class. The research was conducted in 12 meetings in each class. At the first meeting, a preliminary test was given which aims to see to what extent the students' ability limits. The second meeting until the 11th meeting was given a learning process using the Snowball Throwing learning model in the experimental class and conventional learning models in the control class. In the end, at the 12th meeting, each class was given a posttest to see if there was an improvement from the first meeting. Based on the research hypothesis testing at SMK N 3 Tondano on basic automotive engineering subjects with jacking and blocking material, it can be seen that Snowball Throwing learning affects students' mastery of concepts.